Interregional Partnership as a Background for the Sustainable Development: European Facet - Zablodska, Inna; Sieriebriak, Kseniia; Kolomytseva, Olena; Dzhumageldiyeva, Gulnara; Rohozian, Yuliia (European Journal of Sustainable Development, 2019)
Interregional cooperation is a complex system of interconnected processes, which has begun to develop for a very long time and in the last five years, and has become relevant. This fact is also confirmed by the fact that the Association Agreement between Ukraine and the European Union includes a norm on the comprehensive development of interregional cooperation in the strategic perspective and, in most economic and legal issues; it relies on the experience of the European countries, such as Germany and Italy. Studying the world experience and identifying common economic and legal trends in the partnership implementation between regions could help Ukraine to introduce this process in practical terms and possibly avoid the most popular problems in this area. The sphere of interregional cooperation is not only economic sphere; it is a consolidation of the social sphere, economic and ecological, which is the embodiment of sustainable development of each region and the country as a whole. Value / originality. The research presents an analysis of interregional partnership in some European countries (Germany and Italy). The work compares the experience of interregional dispute implementation between the countries based on the strategic documents in this area that are related to sustainable development. Specific statistical and methodological examples of socio-economic development of the above-mentioned countries are presented in the process of establishing interregional ties. The comparative analysis of strategic subregion elements of interregional cooperation are presented and the results of the analysis by means of interval estimation are ranked. Recommendations on implementation the European experience in interregional cooperation for sustainable development in Ukraine are given. For the first time in Ukraine, the sphere of interregional partnership is analyzed not only in the light of the economy, but also through a comprehensive consideration of its economic and legal preconditions. It is expedient to use this approach, because it could be used for calculating not only the economic trends of the development of this sphere of cooperation, but also for paying attention to its legal regulation (due to the Association Agreement between Ukraine and the EU, in which interregional cooperation is one of the central places for sustainable development). Subsequently, based on these results, it would be possible to develop practical recommendations for the harmonization of Ukrainian legislation in accordance with EU legislation, which would include the economic mechanisms for the functioning of interregional cooperation and sustainable development in Ukraine. Keyword Set: World experience, economic and legal foundations, interregional cooperation, development, strategy